The impact of esketamine on cardiac function in patients undergoing anesthesia - Edward Sun; Yuxian Liu; Jingping Wang (Exploration of Medicine, 2025)
Esketamine, the S-enantiomer of ketamine, has gained prominence as an adjunct in pain management during general anesthesia due to its higher potency and ability to achieve therapeutic effects at lower doses than ketamine. While its benefits for pain relief and mental health are well-established, the specific effects of esketamine on cardiac function during anesthesia remain under investigation. Anesthesia itself induces physiological changes in the cardiovascular system, and esketamine can exacerbate these effects by increasing sympathetic activity, heart rate, blood pressure, and cardiac output. Additionally, it can induce peripheral vasoconstriction, raising systemic vascular resistance. These cardiovascular effects are particularly concerning in patients with pre-existing heart conditions, underscoring the importance of preoperative assessment, continuous monitoring, and potential dose adjustments. This review examined the hemodynamic effects of esketamine, the associated cardiovascular risks, and the clinical implications for patients with cardiac conditions, offering recommendations for its safe use in anesthesia.